Fecal microbiota transplantation in children: current concepts. Issue 5 (October 2019) - Gurram, Bhaskar; Sue, Paul K.
Abstract : Purpose of review: Administration of fecal material into the gastrointestinal tract, termed fecal microbiota transplantation (FMT), is increasingly recognized as an effective treatment option for recurrent Clostridium difficile infection (RCDI). The impact of FMT on host microbial communities and subsequent disease states has also been explored in recent years for conditions as varied as inflammatory bowel disease especially ulcerative colitis, metabolic diseases, such as diabetes, graft-versus-host disease in hematopoietic stem cell transplant recipients, and autism and autism spectrum disorders. The purpose of this article is to review the evidence for FMT as a treatment option in various pediatric illnesses. Recent findings: The rate of C. difficile infection is rising among children, and is associated with significant morbidity and disease, with recurrence in up to 20% of pediatric patients. Several randomized controlled trials evaluating the utility of FMT in RCDI in comparison to vancomycin have been published and demonstrate high rates of efficacy between 70 and 100%. In addition, the safety of FMT in the treatment of RCDI has been well described in the adult population, with several pediatric case series demonstrating similar rates of tolerability and adverse events. FMT in ulcerative colitis appears promising, especially with multiple infusions administered via the lower gastrointestinal tract. However, there are several limitations, including the lack of uniformity of protocols used, source of FMT, route of administration and the lack of standardization of concomitant therapies. The data on usage of FMT for other indications are preliminary and limited. Summary: FMT is recognized as an effective treatment option for RCDI and is increasing sought by parents. Although limited, pediatric studies to date on the use of FMT for RCDI demonstrate similar efficacy rates as in the adult population. FMT has been proposed as a treatment option for an increasing number of pediatric conditions, and additional studies are needed to delineate the efficacy of FMT outside of RCDI, as well as its short and long-term impacts on human health.